Ação da triiodotironina na criação de larvas da piracanjuba (Brycon orbignyanus) e do matrinxã (Brycon cephalus) - Leonardo, Antonio Fernando Gervásio [UNESP] (2005)
This work evaluated the effect of the triiodotironine (T3) on the hatching, growth and survival of larvae of piracanjuba, Brycon orbignyanus, in 12 days of culture in laboratory. After extrusion, oocytes of 5 females were fertilized and divided in 4 batches for hydration with the solutions (treatments): H1 (control - water); H2 (0.01ppm T3); H3 (0.05ppm T3) and H4 (0.1ppm T3). The highest number of hatched larvae was obtained with 0.01 and 0.05 ppm of T3 and the lower number with the highest dose (0.1 ppm). At the hatching, the biggest larvae were found in the T3 treatments. Thirty-six h post-hatching (hph), larvae were transferred to aquaria where they remained for 12 days, feeding zooplankton + ration. From the transferring to the 9º day of culture, larvae exposed to T3 had higher weight and length, especially those exposed to 0.05 ppm. At 12° day, larvae of all treatments had similar sizes. The specific growth rate was higher in T3 treatments until 6o day, but after 12 days it was similar in all treatments, indicating higher growth rate until 6° day. The coefficient of variation of weight (CVw) and length (CVl), used to verify size homogeneity of larvae, was higher in control larvae, sugesting that T3 promoted lower size difference in larvae, at the incubation, especially in 0.05ppm T3 larvae. From 36 to 60 hph there was intense predation in all treatments and about 40% of the larvae had rests of larvae in the stomach. At 12° day, survival did not differ among treatments (55.0, 50.1 and 50.0%, in H1 H2 H3, respectively). This study suggests that T3 can have beneficial effect in growth of piracanjuba larvae. Besides higher number of larvae, the increase of larvae weight and length at 9º day of culture allows better conditions of survival at the transferring from the laboratory for the outdoor tanks